PHYSIOTHERAPY MANAGEMENT IN PRE-POST TOTAL HYSTERECTOMY ET CAUSA ENDOMETRIAL CANCER: CASE REPORT - Zirly Zayyinah Zakiah; W Wahyuni; Nurul Muflihah (CV. Fahr Publishing, 2026)
Endometrial cancer (CA) is a cancer that originates from the inner lining of a woman's uterus and is the most common gynecological cancer experienced by women. The standard treatment for patients with early-stage endometrial cancer is hysterectomy, which is a procedure to remove the uterus. One approach in performing hysterectomy is the abdominal approach. The purpose of this study was to evaluate changes in pain (NRS), functional activity (Kenny Self-Care), muscle strength (MMT), and digestive function after the provision of pre- and postoperative physiotherapy interventions in one patient who underwent a total hysterectomy with an abdominal approach. The research method used a case report or case report on a 70-year-old female patient during pre/before and post/surgery total hysterectomy with a total of 3 meetings at PKU Muhammadiyah Hospital Yogyakarta. The exercises given to the patient were breathing exercises, isometric abdominal exercises, Kegel exercises, mobilization exercises, and exercises to help restore digestive function. The evaluation results in this case report showed clinical changes in pain parameters (Numeric Rating Scale), muscle strength (Manual Muscle Testing), functional activity (Kenny Self-Care), and subjective assessment of digestive function in this patient. In conclusion, early exercise is effective in reducing pain and anxiety, improving physical function, and accelerating recovery after hysterectomy according to the principles of Enhanced Recovery After Surgery (ERAS) in this case report.